Comparative Analysis of the Altman and Zmijewski Models for Predicting Financial Distress Conditions of Textile and Garment Companies Listed on the IDX 2020-2024 - Gulo, Jalinan Kristina; Rosyidasari, Fadlilah; Darmayanti, Yeasy (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to analyze the financial health of textile and garment companies listed on the Indonesia Stock Exchange during the 2020–2024 period and compare the accuracy of two bankruptcy prediction models, the Altman Z-Score and the Zmijewski model. The study was conducted on eight companies by calculating the financial ratios of each company and then classifying them into safe, gray, or distress zones. The analysis results show that companies BELL, INDR, SSTM, and TFCO are consistently in the safe zone according to both models. Meanwhile, ARGO, HDTX, and SRIL are included in the distress category, with scores indicating a high bankruptcy risk. Company ESTI showed different results, being in the distress zone according to Altman, but showing financial improvement according to the Zmijewski model since 2021. The conclusion of this study is that the combination of the two models can provide a more comprehensive picture of a company's bankruptcy risk level and can be used as a tool in managerial decision-making and investment considerations.